A comparison of infrared, Raman, and coherent Raman spectroscopies in studies of shock-induced chemistry - Moore, David S.; Bolme, Cynthia A.; Brown, Kathryn E.; Greenfield, Margo T.; McGrane, Shawn D. (AIP conference proceedings, 2020)
Vibrational spectroscopy allows identification of molecules with very high specificity. It is therefore often applied for the measurement of species under shock compression, especially when chemical reactions are likely such as in energetic materials. There are unique complications for these vibrational spectroscopic methods in the applications to shock-compressed materials, which are the subjects of this paper. The complications illustrated and discussed here include band-broadening mechanisms, thin film interference effects, signal integration along a path through shocked and unshocked layers, convolutions of signal path integration with reaction rates, and the non-resonant background in CARS.